Analisis Kehilangan Air dengan Metode Neraca Air dan Infrastructure Leakage Index (ILI) pada Perumda Air Minum Kota Surakarta - Galih Iman Rakhmad; Adhi Yuniarto (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Non-revenue water is the main problem faced by Perumda Air Minum Kota Surakarta, with a water loss rate reaching 42.37% in 2022. The purpose of this study is to identify and control the physical water loss using the water balance method and infrastructure leakage index. Primary data was obtained through field visits to make direct measurements, while secondary data was obtained based on data from the Solo City Drinking Water Company. A water balance analysis was carried out to determine the physical water loss, which was then used to calculate the ILI. The results showed that the water distribution volume was 24,270,430 cubic metres and the physical water loss was 9,669,609 cubic metres. The ILI value illustrates the effectiveness of distribution network management in controlling water losses. The conclusion of this study highlights the importance of water-free control measures and reduction of physical water leakage/loss to improve the efficiency and operational quality of drinking water services in Surakarta City.